Luminescent Sensing of 1,3,5-Trinitrotoluene Using a Schiff Base Ligand and Cd(II) Complex: Structural and Photophysical Investigations - Turan, Nevin; Altun, Ayhan; Buldurun, Kenan; Aydin, Olcay (Wiley, 2025)
The Schiff base (H2L) was synthesized by condensing 2-amino-6-methyl-4,5,6,7-tetrahydrothieno[2,3-c]pyridine-3-carboxamide with 5-bromo-2-hydroxybenzaldehyde in a 1:2 M ratio, yielding the product with high efficiency. This Schiff base then formed a coordination complex with Cd(II) in a 1:1 M ratio, resulting in the complex [H2LCd(H2O)2]1.5H2O. The synthesis and structural characterization of H2L and its Cd(II) complex were carried out using various techniques, including microanalysis (CHNS), FTIR, 1H and 13C-NMR, mass, UV-visible, magnetic susceptibility, thermogravimetric analysis (TGA), and fluorescence spectroscopy. The spectral data suggested that the Cd(II) complex adopted an octahedral geometry. In addition to the structural studies, the fluorescence properties of H2L and its Cd(II) complex were investigated. Sensor properties of the Cd(II) complex for detecting nitroaromatic compounds were assessed using fluorescence spectroscopy. Both compounds exhibited high sensitivity for the detection of 1,3,5-trinitrotoluene (TNT). Specifically, H2L demonstrated a low limit of detection (LOD) of 0.094 mu M in the linear range of 1-10 mu M. The fluorescence studies revealed that H2L and its Cd(II) complex displayed strong fluorescence emissions. Furthermore, the Schiff base was employed for detecting TNT through fluorescence quenching, showing excellent selectivity and sensitivity.
Keywords: Cd(II) complex; fluorescence emission; NACs; Schiff base; spectroscopy; TNT